Becoming Job-Ready? Narratives of Local Welfare-to-Work Programs and Client Experiences Across Differing Economic Contexts in California. Issue 4 (October 2022) - Lanfranconi, Lucia M.; Das, Aditi; Subaran, Joy; Malagon, Patricia
Previous research on welfare-to-work exits has focused on individual client characteristics rather than local economic contexts. Drawing on a qualitative comparative case study design, this study enhances our understanding on how welfare-to-work organizational narratives and client experiences of becoming job-ready are shaped across two different economic contexts. In the disadvantaged economic context, a punitive welfare-to-work narrative is operational resulting in clients accepting precarious work. In the more privileged economic context, the individual responsibility narrative dominates as clients struggle to make ends meet. Our findings highlight how regional economic factors shape organizational narratives and impel clients to accept precarious low wage working conditions and unstable housing. Thus, there is a need for alternatives to welfare-to-work, such as unconditional, Universal Basic Income.